2016
DOI: 10.1123/tsp.2013-0076
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Attentional Foci and their Temporal Patterns: A Naturalistic Study in Expert Figure Skaters

Abstract: This study aimed to explore attentional foci and their temporal patterns in expert skaters in real competition situations. Individual self-confrontation interviews were held with 8 expert figure skaters while they watched their videotaped program performed in official competitions. Qualitative data analysis revealed that skaters used a substantial number of foci, which were classified by content and characteristics. Event listing was used to display the patterns of foci over time, revealing that skaters used d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 27 publications
7
29
0
Order By: Relevance
“…These discrepant findings have raised debate on the utility of an external focus for all tasks (Peh, Chow, & Davids, 2011) and for populations that have been understudied (e.g., older adults at risk for falling) . Second, attention is dynamic (Hutchinson & Tenenbaum, 2007) and focus is rarely static throughout a single training session (Bernier, Trottier, Thienot, & Fournier, 2016;. Thus, to conclude that providing one "dose" of external focus instruction will remain as the prominent focus over multiple practice sessions and elicit long term changes in motor learning is unsubstantiated.…”
Section: Introductionmentioning
confidence: 99%
“…These discrepant findings have raised debate on the utility of an external focus for all tasks (Peh, Chow, & Davids, 2011) and for populations that have been understudied (e.g., older adults at risk for falling) . Second, attention is dynamic (Hutchinson & Tenenbaum, 2007) and focus is rarely static throughout a single training session (Bernier, Trottier, Thienot, & Fournier, 2016;. Thus, to conclude that providing one "dose" of external focus instruction will remain as the prominent focus over multiple practice sessions and elicit long term changes in motor learning is unsubstantiated.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, Abdollahipour et al (2015) 67 focus discussion on theory and laboratory/fundamental research findings (e.g., Kal, van der 68 Kamp, & Houdijk, 2013;Land, Frank, & Schack, 2014;Wulf, Höß, & Prinz, 1998) Indeed, elite-level athletes report beneficial effects from focussing on aspects of the 88 movement (e.g., Bernier, Trottier, Thienot, & Fournier, 2015;Carson, Collins, & 89 MacNamara, 2013;MacPherson, Collins, & Morriss, 2008;Nyberg, 2015;Orlick & 90 Partington, 1988;Robazza & Bortoli, 1998) and, sport psychologists often employ explicit 91 movement imagery techniques to enhance competitive performance (e.g., Carson,Collins,& 92 Jones, 2014; Collins, Morriss, & Trower, 1999;Martindale & Collins, 2012;Wang & Zhang, 93 2015). Accordingly, failure to contextualise the study within current coaching/sport 94 psychology practices, or to explain why athletes' perceptions are apparently wrong, surely 95 limits the paper's ability to serve its purpose in a purportedly applied discipline.…”
mentioning
confidence: 99%
“…For example in the study by Bernier et al (2015) 113 one elite-level ice skater reported "during the approach to the jump, actually, I'm doing the has the potential to be unfamiliar in that it may conflict with useful imagery that is ordinarily 118 employed (cf. our comments in the previous paragraph).…”
mentioning
confidence: 99%
“…Expert batters employ routines, both behavioural and cognitive, in between deliveries to manage these pressures. Similar to the research findings on performance routines [43,44], this suggestibly allows experts to manage more effectively their emotions; attentional focus [45,46]; concentration [47] and enhance consistency of performance [48,49]. Interestingly, a crucial aspect of the pre-performance routine literature is said to involve being able to channel attention from irrelevant thoughts to task-specific thoughts.…”
Section: Discussionmentioning
confidence: 53%